Hawk Eye: A logical innovative technology use in sports for effective decision making - Singh Bal, B.; Dureja, G. (Sport Science Review, 2012)
The present study aims at explaining hawk eye technology in sports with regard to their latest trends in the sporting arena. This is one of the most commonly used technologies in the various sports. It has been put to a variety of uses, such as providing a way to collect interesting statistics, construct very suggestive visual representations of the game play and even helping viewers to better understand the umpiring decisions. The Hawk-eye is one such technology which is considered to be really top indentation in various sports. The necessary idea is to monitor the trajectory of the ball during the entire duration of play. We will see how the Hawk-eye technology successfully treats each of these issues and provides a robust system to be used in practice. The Hawk-eye system was developed as a replay system, originally for TV Broadcast coverage. We have thus seen that the Hawk-eye is a great innovation, which puts technology to good use in the field of sports. The international scenario of hawk eye has been discussed while analyzing the data of hawk eye software for reliable decision. The technology is used widely these days, in sports such as Tennis and Cricket. The accuracy which can be achieved with the use of the system is making the authorities think seriously about reducing the human error component involved in important decisions. Hawk eye (artificial judgement) is very excellent and superb decision making power as compared to human being (natural judgement). Hawk-Eye software team is already working on the implementing system for basketball, football, badminton and snooker.